Estimate of the functional size in the requirements elicitation - Bertolami, Mabel Angélica; Oliveros, Alejandro (2005)
Early measurement of software size allows to estimate costs and effort as well as to plan the development schedule. In previous reports, an approach which applies the Function Points Analysis to the derivative Scenarios of the Language Extended Lexicon was presented. In the process of the validation of that proposal, statistical techniques were applied on a subset of the obtained data from the measurement of several cases of study. In this article, a linear regression analysis which allowed establishing an estimate model of the scenarios functional size and the verification of the validity of that model is presented. The results are encouraging as for the feasibility of the model and its possible subsequent refinements.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
Journal of Computer Science & Technology, 5(2), pp. 80-86.
Keywords: DESARROLLO DE SOFTWARE